Pengembangan LKPD berbasis etnomatematika motif batik pada materi bangun datar di Sekolah Dasar - Miftah Nur Kholifah; Dindin Abdul Muiz Lidinillah; Muhammad Rijal Wahid Muharram (IKIP Siliwangi, 2026)
Abstract This research aims to develop teaching materials in the form of ethnomathematics-based LKPD on plane figures in elementary schools. Based on the results of the preliminary study, problems in mathematics learning were found, such as lack of interest from students and lack of creativity in using teaching materials. The solution to this problem is to develop LKPD based on batik motif ethnomathematics. The method used in this research is the EDR (Educational Design Research) development research method with three stages, namely analysis and exploration, design and evaluation and reflection. The data collection techniques used were interviews, observation, documentation, expert validation questionnaires, student response questionnaires, and teacher response questionnaires. The results of the validation show that the score obtained from didactic experts was 94.44%, was obtained in the very appropriate category, and from technical experts a score was obtained of 93.33% in the very appropriate category. Meanwhile, the results of student responses obtained an average score of 93% in the very practical category and the results of the teacher response questionnaire obtained an average score of 92% in the very practical category. Based on the research results, LKPD based on ethnomathematics of batik motifs is very feasible and very practical to use to make it easier for students to study flat shape material in elementary schools. Keywords: Ethnomathematics, Elementary schools, LKPD Abstrak Penelitian ini bertujuan untuk mengembangkan bahan ajar berupa LKPD berbasis etnomatematika pada materi bangun datar di sekolah dasar. Berdasarkan hasil studi pendahuluan diperoleh temuan permasalahan dalam pembelajaran matematika seperti kurangnya minat dari peserta didik dan kurangnya kreatifitas dalam penggunaan bahan ajar. Solusi dari permasalahan tersebut adalah dengan mengembangkan LKPD berbasis etnomatematika motif batik. Metode yang digunakan dalam penelitian ini yaitu metode penelitian pengembangan EDR (Educational Design Research) dengan tiga tahapan yakni analisis dan eksplorasi, desain dan serta evaluasi dan refleksi. Teknik pengumpulan data yang digunakan adalah dengan wawancara, observasi, dokumentasi, angket validasi ahli, angket respon siswa, dan angket respon guru. Hasil dari validasi menunjukkan perolehan skor yang didapat dari ahli didaktik adalah sebesar dengan 94,44%, dan dari ahli teknis diperoleh skor sebesar 93,33% dengan kategori sangat layak. Sementara hasil dari respon siswa diperoleh skor rata-rata sebesar 93% dengan kategori sangat praktis dan hasil dari angket respon guru diperoleh skor rata-rata sebesar 92% dengan kategori sangat praktis. Berdasarkan hasil penelitian, LKPD berbasis etnomatematika motif batik sangat layak dan sangat praktis digunakan untuk memudahkan siswa dalam mempelajari materi bangun datar di sekolah dasar. Kata Kunci: Etnomatematika, Sekolah Dasar, LKPD